Are students with disabilities ready for college? The influence of college readiness to college engagement - Alies Poetri Lintangsari; Ive Emaliana; Fatmawati Fatmawati; Unita Werdi Rahajeng (Institute of Advanced Engineering and Science, 2021)
Inclusive education is seen as promising way to accommodate students with disabilities in accessing higher education; yet, the implementation leaves challenges for the students with disabilities and also the faculties. Regarding the secondary education curriculum that is not preparing students with disabilities to attend higher education, students with disabilities are struggling in adjusting college life. This research aimed at confirming the influence of college readiness to college engagement of students with disabilities. There were 61 college students with disabilities participated in the survey on college readiness and college engagement. Independent T-Test and simple regression analysis was applied to test the hypothesis. The result showed that the college readiness influence college engagement with large effect size (r=.769>0.50, F=85.494, p (.000) <0.01) which indicates that the more students are college-ready, the more they are engaged. Subsection’s variables of gender and education background do not statistically significant affect the college readiness and engagement of students with disabilities. As the opportunity for students with disabilities attending college is uprising, college transition program is highly suggested to prepare students with disability for college life.